Postponement of General Elections in Crisis Situations: Legal Analysis, History, and Implications for Democracy - Putri, Nabila Diara; Irwan Triadi; M. Adnan Madjid (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the historical of general election postponements in Indonesia, along with the legal basis and constitutional implications of delaying elections without a legitimate emergency. As the primary instrument of popular sovereignty, elections must be held periodically, fairly, and in accordance with the constitution. In this regard, postponing an election without a solid legal foundation could trigger legitimacy crises and constitutional disputes. The method used in this study is normative juridical research with a statute, conceptual approach and historical approach, with the data analyzed qualitatively and descriptively. The novelty of this study lies in its comprehensive review of the historical dynamics and legal framework surrounding election postponements from the era of Parliamentary Democracy to the Reform Era with a specific focus on the legal gap in responding to non-natural disasters such as the COVID-19 pandemic. The findings reveal that election postponements in Indonesia have often been linked to political and security crises, though not always grounded in a democratic legal process. The results of this study show that the postponement of elections in Indonesia has historically been influenced by political instability, legal ambiguity, and emergency situations, such as armed conflict or the COVID-19 pandemic. Despite these challenges, the legal framework in Indonesia lacks specific provisions regarding systematic election postponement, especially in the case of non-natural disasters. The ambiguity in interpreting terms like “other disturbances” under existing electoral laws has led to varying legal opinions and uncertainty in implementation. The conclusion of this study is that the postponement of elections can only be justified in the presence of a real and constitutionally recognized state of emergency. The absence of a clear legal framework poses a risk to democratic integrity and public trust. Therefore, the study emphasizes the urgent need to revise and strengthen electoral regulations by clearly outlining the procedures, legal basis, and conditions under which elections may be postponed, ensuring the protection of citizens’ constitutional rights in all circumstances.